Development of a novel denitrifying phosphorus removal and partial denitrification anammox (DPR + PDA) process for advanced nitrogen and phosphorus removal from domestic and nitrate wastewaters. (May 2021) - Wu, Peng; Zhang, Xingxing; Wang, Yuguang; Wang, Chaochao; Ma, Liping; Wani Victor Jenario, Francis; Liu, Wenru; Xu, Lezhong
Graphical abstract: Highlights: Deeper-level N (97.57%) and P (95.66%) removal was obtained in a DPR + PDA process. A significant removal ratio of P (96.10%) and N (58.65%) was taken over via DPR. PDA contributed to N removal accounted for 37.07% with anammox as fundamental. High efficient PD (97.67%) allowed a high N removal via coexisted PD and anammox. Reductions of influent organic and nitrate devoted the augmented P metabolic rates. Abstract: A novel energy-efficient DPR + PDA (denitrifying phosphorus removal and partial denitrification anammox) process for enhanced nitrogen and phosphorus removal was developed in the combined ABR-CSTR reactor. After 220 days operation, excellent total inorganic nitrogen (TIN) and phosphorus removal (97.57% and 95.66%, respectively) were obtained under external C/NO3 − -N of 0.7, with the effluent TIN and PO4 3− -P concentrations of 3.51 mg/L and 0.28 mg/L, respectively. At the steady period, DPR contributed major TN removal (58.65%), while PDA mediated an increasingly considerable impact and finally achieved 37.07%, in which anammox accounted for a significant percentage. Batch tests demonstrated that efficient PD with nitrate-to-nitrite transformation ratio of 97.67% supplying stable nitrite for anammox, and phosphorus was mainly removed using nitrate as electron acceptor via DPR with the ideal phosphorus release/uptake rate (7.73/22.17 mgP/gVSS/h). Accumulibacter (6.24%) dominated high phosphorus removal performance, while Thauera (8.26%) and Candidatus Brocadia (2.57%) represented the superior nitrogen removal performance.